2021
DOI: 10.1182/blood.2020009564
|View full text |Cite
|
Sign up to set email alerts
|

EBF1 and PAX5 control pro-B cell expansion via opposing regulation of the Myc gene

Abstract: Genes encoding B lineage restricted transcription factors are frequently mutated in B-lymphoid leukemias, suggesting a close link between normal and malignant B-cell development. One of these transcription factors is Early B cell Factor 1 (EBF1), a protein of critical importance for lineage specification and survival of B-lymphoid progenitors. Here, we report that impaired EBF1 function in mouse B-cell progenitors results in reduced expression of Myc. Ectopic expression of MYC partially rescued B-cell expansio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…Thus, the protruding α1-helix within the EBNA2 N-terminal transactivation (END) domain is the structural element of EBNA2 that confers B cell specific cellular activation and is a critical structure. Our study also highlights the role of EBF1 in controlling and regulating proliferation of mature human B cells extending the finding of Somasundaram et al in mouse pro-B cells (Somasundaram et al, 2021).…”
Section: Ebna2 Requires the Interaction With Ebf1 To Access The Viral Lmp1 Promotorsupporting
confidence: 88%
See 1 more Smart Citation
“…Thus, the protruding α1-helix within the EBNA2 N-terminal transactivation (END) domain is the structural element of EBNA2 that confers B cell specific cellular activation and is a critical structure. Our study also highlights the role of EBF1 in controlling and regulating proliferation of mature human B cells extending the finding of Somasundaram et al in mouse pro-B cells (Somasundaram et al, 2021).…”
Section: Ebna2 Requires the Interaction With Ebf1 To Access The Viral Lmp1 Promotorsupporting
confidence: 88%
“…As a pioneer factor, EBF1 alters the chromatin signature of B cell precursors allowing additional transcription factors and transactivators the access to chromatin (Boller et al, 2016). Furthermore, EBF1 directly activates MYC in murine pro-B cells to promote proliferation of these cells (Somasundaram et al, 2021). Here, we show that EBNA2 not only requires the pioneer activity of EBF1 to gain access to open chromatin but it tackles and usurps EBF1 in B cells to access its response elements and to activate direct target genes of EBNA2 such as MYC and LMP1.…”
Section: Ebna2 Requires the Interaction With Ebf1 To Access The Viral Lmp1 Promotormentioning
confidence: 99%
“…Maintenance of the B lineage program not only prepares B cell progenitors for additional differentiation to produce antibody-secreting cells but may also serve as a barrier against malignant transformation of B cells. [47][48][49] Expression of early B cell markers is coupled with the onset of immunoglobulin (Ig) gene assembly by V(D)J recombination. The generation of functional Ig loci proceeds stepwise, resulting in expression of the B cell-specific receptor for antigen (BCR) and functional antibody proteins for secretion in response to infection (reviewed in 50).…”
Section: Overvie W Of B Cell De Velopment In the Bone Marrowmentioning
confidence: 99%
“…74 PAX5 physically interacts with NuRD components, as detected following pull-down and mass spectrometry experiments. 75 PAX5 negatively regulates expression of c-Myc, 48,49 which may be important for prevention of B cell leukemias. In this regard, previous studies on the induction of pluripotency suggest a potential role of NuRD in the maintenance of the B cell fate.…”
Section: Chd 4 -Dependent Mechanis Ms Control Chromatin S Truc Ture and Tr An Scrip Ti On In E Arly B Cell Prog Enitor Smentioning
confidence: 99%
“…Both EBF1 and PAX5 are bound to MYC enhancers in mouse pro-B cells as well as pro-B ALL NALM6 cells. While EBF1 promoted MYC expression, PAX5 negatively regulated MYC levels in normal B-cell progenitors [283]. Although it is not clear how this regulation looks in malignant cells, another report suggested that EBF1 and PAX5 prevent malignant transformation by limiting MYC levels [284].…”
Section: Exploiting Enhancers By Deregulated Transcription Factorsmentioning
confidence: 99%